2008
DOI: 10.1177/0009922807306166
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Avoidable Pediatric Hospitalizations as Defined by the Agency for Healthcare Research and Quality: What Do They Tell Us About Disparities in Child Health?

Abstract: This study was conducted to determine if the Agency for Healthcare Research and Quality's newly established pediatric quality monitors, which measure potentially avoidable hospitalizations, are useful in detecting disparities in health care delivery. Data for all hospital discharges in Tennessee in 2002 were evaluated for the 5 pediatric discharge monitors identified by the Agency for Healthcare Research and Quality. These diagnoses were asthma, short-term complications of diabetes, gastroenteritis, urinary tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
1
16
1
Order By: Relevance
“…3 The $304 million in charges and 71 444 hospital days per year attributed to potentially preventable admissions in this study in Texas, the nation' s second largest state with 8.5% of the US population, 20 are proportional with estimates of $4 billion and 1 million hospital-days in 1 year in the 38 states in the Kids' Inpatient Database. 2 Similar to previous studies, 2,3,12 we found that black and Hispanic children had higher odds of potentially preventable admissions than white children who were hospitalized. Race and ethnicity have also been reported as risk factors for pediatric readmissions 21,22 and potentially preventable admissions for adults.…”
Section: According To Diagnosissupporting
confidence: 87%
See 3 more Smart Citations
“…3 The $304 million in charges and 71 444 hospital days per year attributed to potentially preventable admissions in this study in Texas, the nation' s second largest state with 8.5% of the US population, 20 are proportional with estimates of $4 billion and 1 million hospital-days in 1 year in the 38 states in the Kids' Inpatient Database. 2 Similar to previous studies, 2,3,12 we found that black and Hispanic children had higher odds of potentially preventable admissions than white children who were hospitalized. Race and ethnicity have also been reported as risk factors for pediatric readmissions 21,22 and potentially preventable admissions for adults.…”
Section: According To Diagnosissupporting
confidence: 87%
“…25 Inequalities in access to care may also contribute but would be expected to be more equal across conditions. Surprisingly, privately insured children had the highest odds that their admission was potentially preventable, with government insurance decreasing odds by 27% and being uninsured decreasing odds by 7%, whereas previous research has shown that uninsured 6 or publicly insured 12 children are more likely to have potentially preventable admissions than privately insured children. Patients with private insurance theoretically have better access to primary and preventative care 26 and, therefore, lower rates of potentially preventable admissions.…”
Section: According To Diagnosismentioning
confidence: 56%
See 2 more Smart Citations
“…[1][2][3][4] Individual health is negatively affected by socioeconomic stressors, leading to poor health and higher health care utilization. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The complex interplay of clinical, social, and other factors is illustrated in Fig 1. 25 Children from low socioeconomic status (SES) families have myriad health problems. 5,13,20,21 Among adults with chronic conditions, lower SES has been associated with longer hospital lengths of stay (LOS), higher costs of care, 12,18 and higher risk of hospital readmissions.…”
mentioning
confidence: 99%